EXPERIENCE OF FOREIGN COUNTRIES IN TRAINING NURSES - MANSUROVA GULNOZA MUYINJONOVNA; ABDULLAYEVA SHOHSANAM NASRULLOYEVNA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Global healthcare issues have always demanded diverse perspectives, and the need for healthcare workers to communicate globally about industry needs, ideas, and solutions is more urgent than ever. Many study abroad programs specifically cater to nursing students, offering valuable international experience and insights into global healthcare. These programs enable students to examine the cultural, political, and economic forces shaping healthcare systems worldwide, fostering both personal and professional growth.